Following the phase transitions of iron in 3D with X-ray tomography and diffraction under extreme conditions. (15th June 2020) - Boulard, Eglantine; Denoual, Christophe; Dewaele, Agnès; King, Andrew; Le Godec, Yann; Guignot, Nicolas
Graphical abstract: Abstract: Transformations of iron at high pressure and temperature has significant implications in Fe-based materials technology as well as in planetary science due to its prominent presence in terrestrial planet cores. However, a detailed understanding of processes involved in the high temperature α -Fe ↔ γ -Fe and the high pressure α -Fe ↔ ϵ-Fe transformations is still lacking. In this study, we monitored in situ the orientations and mobility of the interfaces of coexistence of parent and daughter phases of iron upon transitions around the α − γ − ϵ triple point. We show that in α -Fe ↔ ϵ-Fe transitions, a displacive mechanism induces typical martensitic microstructures, but is followed by a second likely reconstructive step which transforms most of the sample. Under similar pressure, temperature and heating rate conditions, α -Fe ↔ γ -Fe transformations appear to be purely reconstructive. This work provides for the first time a complete 3D microstructural in situ characterization of iron structural transitions under extreme conditions that clarifies their fundamental mechanisms.